Neutrophil extracellular traps and reactive oxygen species: Predictors of prognosis in bladder cancer - Mansourabadi, Zahra; Assarehzadegan, Mohammad-Ali; Mehdipour, Fereshteh; Ariafar, Ali; Faghih, Zahra; Safari, Elahe (Immunology letters, 2025)
•Early NETosis of circulating neutrophils was associated with early phase of tumor progression and good prognosis in patients with bladder cancer.•ROS production of circulating neutrophils revealed prognostic significance for early detection and monitoring of the patients with bladder cancer.•Early NETosis was not correlated to ROS production. Neutrophils, the most abundant leukocytes in circulation, have become the subject of intensive research due to growing evidence of their role as modulators of cancer with both anti- and pro-tumorigenic effects. However, their prognostic function related to the release of neutrophil extracellular traps (NETs) and production of reactive oxygen species (ROS) has not yet been elucidated in the context of bladder cancer (BC). This study aimed to evaluate the ability of circulating neutrophils from BC patients to undergo NETosis and produce ROS—both spontaneously and following activation with phorbol 12-myristate 13-acetate (PMA)—using flow cytometry and immunofluorescence techniques. Their relevance to clinicopathological characteristics was also evaluated. Our results showed that PMA-treated neutrophils had increased early NETosis in patients with stage II (P = 0.048) and T2 (P = 0.014) compared to those with stage III and T3, respectively. These cells also showed a significant increase in ROS production in patients with T2 compared to those with T3 (P = 0.026) and T4 (P = 0.014), as well as in patients with stage II compared to stage IV (P = 0.048). Additionally, spontaneous ROS production was higher in patients without lymphovascular invasion than in those with invasion (P = 0.013). The increased activity of neutrophils observed in earlier stages (stage II and T2) suggests a potential protective mechanism in the early phases of cancer progression. It also highlights NETosis and ROS production by neutrophils as possible biomarkers for assessing disease progression. These findings provide insights into the complex interactions of neutrophils within the tumor microenvironment and lay the groundwork for further investigations into targeted therapies, potentially improving prognostic evaluations and treatment outcomes for patients.